2022
DOI: 10.14573/altex.2107051
|View full text |Cite
|
Sign up to set email alerts
|

Grouping of UVCB substances with dose-response transcriptomics data from human cell-based assays

Abstract: The application of in vitro biological assays as new approach methodologies (NAMs) to support grouping of UVCB (unknown or variable composition, complex reaction products, and biological materials) substances has recently been demonstrated. In addition to cell-based phenotyping as NAMs, in vitro transcriptomic profiling is used to gain deeper mechanistic understanding of biological responses to chemicals and to support grouping and read-across. However, the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…ECHA has included petroleum substances in the restriction roadmap (pool 2) 8 , which means that test data are critically important. The attempt to reduce the number of tests by grouping through biological similarity by House et al (2022) did not really work out, showing that "transcriptomics data provide … only modest additional value for grouping". In other words, possible additional processing steps such as solvent extraction, hydro-desulfurization, or hydrogenation (McKee et al, 2015).…”
Section: Breakdown By Tonnagementioning
confidence: 99%
“…ECHA has included petroleum substances in the restriction roadmap (pool 2) 8 , which means that test data are critically important. The attempt to reduce the number of tests by grouping through biological similarity by House et al (2022) did not really work out, showing that "transcriptomics data provide … only modest additional value for grouping". In other words, possible additional processing steps such as solvent extraction, hydro-desulfurization, or hydrogenation (McKee et al, 2015).…”
Section: Breakdown By Tonnagementioning
confidence: 99%
“…Machine-learning was used to predict geographic and source rock categories for each oil based on the IMS-MS chemical profiles for all oils tested in each iteration of the analysis as described in previous studies (House et al, 2021(House et al, , 2022Tibshirani et al, 2002). The PAM procedure (Tibshirani et al, 2002), originally developed for tumor classification based on gene expression microarray data, is well-suited for general multi-category classification based on multivariate inputs.…”
Section: Category Prediction Via the Supervised Prediction Analysis O...mentioning
confidence: 99%
“…Because clustering analysis (e.g., unsupervised analysis) with all IMS-MS data was not successful in replicating predetermined groupings, we then investigated whether IMS-MS data could be used to classify samples and whether specific constituents may be more predictive of geographic or geological groupings. For this analysis, we used a supervised prediction algorithm (House et al, 2021(House et al, , 2022Tibshirani et al, 2002). We applied a "leave-one-out" approach whereby a statistical model was trained on the IMS-MS chemical profiles from all tested oils except one; then group classification was predicted for the left-out sample.…”
Section: Classification Of Oil Samples Using Ims-ms Data and Identifi...mentioning
confidence: 99%
“…There has been increasing interest in using so-called New Approach Methodologies (NAMs), in particular, human cell-based in vitro models, to provide empirical data on mixtures for use in cumulative risk assessment [ 27 ]. We have previously demonstrated the feasibility of high-throughput in vitro testing of environmental mixtures [ 28 , 29 ], defined mixtures [ 30 ], and complex substances [ 31 , 32 , 33 ]. In particular, using a diverse set of 42 chemicals from the Agency for Toxic Substances and Disease Registry (ATSDR) substance priority list, we found that in 8 different defined mixtures, CA predictions were typically within an order of magnitude of the effects of defined mixtures, but that the accuracy of additivity assumptions varied greatly by phenotype [ 30 ].…”
Section: Introductionmentioning
confidence: 99%